Pengaruh quality management terhadap green innovation dengan intensitas penelitian dan pengembangan sebagai variabel moderasi - Putri Andani, Wa Ode; Dewi, R. Rosiyana (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this research is to examine and analyze the effect of quality management on green innovation with research and development intensity as a moderating variable. This research was conducted using quantitative methods. The data used in this study is secondary data obtained from the Indonesia Stock Exchange. The population used in this study were all manufacturing companies listed on the Indonesia Stock Exchange during 2018-2020. The sample was selected by purposive sampling method so as to produce 17 companies with a total observation of 51 research samples. The analysis technique of this research is Multiple Linear Regression Analysis. Based on the results of the study, it shows that quality management has a significant positive effect on green innovation, the intensity of research and development has a significant and positive effect on green innovation, and the intensity of research and development weakens the relationship between quality management and green innovation.